2009
DOI: 10.1021/ef8011323
|View full text |Cite
|
Sign up to set email alerts
|

Coking of Model Hydrocarbon Fuels under Supercritical Condition

Abstract: Coking of three model compounds of hydrocarbon fuelsn-heptane, cyclohexane, and tricyclo[5.2.1.0 2.6 ]decane (JP-10)sduring their thermal cracking processes under supercritical condition (873.15 K, 4.1 MPa) has been investigated. The product distributions of the thermal cracking are analyzed by gas chromatography-mass spectrometry (GC-MS). The morphology and microstructures of the cokes are characterized by the techniques of scanning electron microscopy (SEM), transmission electron microscopy (TEM), differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 31 publications
2
31
1
Order By: Relevance
“…When the temperature increases further, a lot of carbons deposit on the surface of the fiber-like coke, wrap the coke core, and become bulb like at the end (Figure 3). Xie et al 59 also found that coke in different fuels presents in different shapes. Coke in n-heptane, cyclohexane, and JP-10 are like fibers, tubes, and granules, respectively.…”
Section: Coking Mitigationmentioning
confidence: 98%
See 1 more Smart Citation
“…When the temperature increases further, a lot of carbons deposit on the surface of the fiber-like coke, wrap the coke core, and become bulb like at the end (Figure 3). Xie et al 59 also found that coke in different fuels presents in different shapes. Coke in n-heptane, cyclohexane, and JP-10 are like fibers, tubes, and granules, respectively.…”
Section: Coking Mitigationmentioning
confidence: 98%
“…DeWitt et al 58 have found that sulfur and sulfide have a significant promotion effect on coking. Xie et al 59 have compared the coking quantities of n-heptane, cyclohexane, and JP-10 under supercritical state (873 K, 4.1 MPa) and found that chemical structure has a great effect on coking.…”
Section: Coking Mitigationmentioning
confidence: 99%
“…Most interestingly, the morphologies of the cokes were very different, as seen in the flaky carbon deposits in Figure 7a and the irregular carbon particles in Figure 7b. A large number of studies have shown that these cokes are amorphous carbon deposits owing to the non-catalytic coking [32,33]. The result suggested that the morphology of non-catalytic cokes is not only affected by the temperature, pressure, and coking precursor, but is also closely related to the surface state of the coatings.…”
Section: The Anti-coking Properties Of Tin and Tio 2 Coatingsmentioning
confidence: 99%
“…low-density polyethylene) in a quartz semi continuous feed reactor with fast heating to obtain solid carbons [4,5]. In recent years, the thermal decomposition of hydrocarbon fuel in hypersonic aircrafts is also a research hotspot, because hydrocarbon fuel is required not only for the propulsive power but also as a coolant with high cooling capacity due to its endothermic pyrolysis reaction at high temperature [6][7][8]. But, the tradition cracking process need high temperature and cause many environmental related problems.…”
Section: Introductionmentioning
confidence: 99%